Effect of Zinpro 100® in a mineral mixture on gain and incidence of footrot in steers grazing native grass pastures - F.K. Brazle (Kansas Agricultural Experiment Station Research Reports, 1993)
In a 3-year study, crossbred steers averaging 585 lb were allotted to groups given either a control or zinc methionine-supplemented mineral mixture while grazing burned native pastures in early summer. The steers were monitored for weight gain and incidence of footrot. The addition of 100 lb Zinpro 100® (50% zinc methionine) per ton of free-choice mineral mixture improved (P<.06) steer daily gain .08 lb. and reduced the incidence of footrot 55% (5.38 vs. 2.45%; P<.06). The gain benefit could not be attributed entirely to reduced footrot, but appeared to also have a nutritional basis.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Zinc methionine; Zinpro; Footrot; Native grass; Stocker cattle